A Novel Method to Identify the Start and End of the Winter Surge in Demand for Pediatric Intensive Care in Real Time*. Issue 9 (November 2015) - Pagel, Christina; Ramnarayan, Padmanabhan; Ray, Samiran; Peters, Mark J.
Abstract : Objective: Implementation of winter surge management in intensive care is hampered by the annual variability in the start and duration of the winter surge. We aimed to develop a real-time monitoring system that could identify the start promptly and accurately predict the end of the winter surge in a pediatric intensive care setting. Design: We adapted a method from the stock market called "Bollinger bands" to compare current levels of demand for pediatric intensive care services to thresholds based on medium-term average demand. Algorithms to identify the start and end of the surge were developed using Bollinger bands and pragmatic considerations. The method was applied to a specific pediatric intensive care service: the North Thames Children's Acute Transport Service using eight winters of data (2005–2012) to tune the algorithms and one winter to test the final method (2013/2014). Setting: A regional specialized pediatric retrieval service based in London, United Kingdom. Measurements and Main Results: The optimal Bollinger band thresholds were 1.2 and 1 SDs above and below a 41-day moving average of demand, respectively. A simple linear model was found to predict the end of the surge and overall surge demand volume as soon as the start had been identified. Applying the method to the validation winter of 2013/2014 showed excellent performance, with the surge identified from November 18, 2013, to January 4, 2014. Conclusions: We have developed and tested a novel method to identify the start and predict the end of the winter surge in emergency demand for pediatric intensive care. Abstract : Supplemental Digital Content is available in the text.